Pyrene-containing conjugated organic microporous polymers for photocatalytic hydrogen evolution from water. Issue 6 (27th January 2021) - Mohamed, Mohamed Gamal; Elsayed, Mohamed Hammad; Elewa, Ahmed M.; EL-Mahdy, Ahmed F. M.; Yang, Cheng-Han; Mohammed, Ahmed A. K.; Chou, Ho-Hsiu; Kuo, Shiao-Wei
Abstract : Pyrene based conjugated microporous polymers (CMPs) as photocatalysts with promising H2 production efficiencies and very high stability. Abstract : Photoactive conjugated microporous polymers (CMPs) are emerging as porous materials capable of mediating the photocatalytic evolution of H2 from water. In this study, we synthesized three pyrene-based CMPs (Py–F-CMP, Py–TPA-CMP, Py–TPE-CMP) through Sonogashira–Hagihara cross-couplings of 1, 3, 6, 8-tetraethynylpyrene (Py–T, as a common monomer building block) with 2, 7-dibromo-9 H -fluorene (F–Br2 ), tris(4-bromophenyl)amine (TPA–Br3 ), and 1, 1, 2, 2-tetrakis(4-bromophenyl)ethene (TPE–Br4 ), respectively, in the presence of Pd(PPh3 )4 in DMF/Et3 N. We then characterized the chemical structures, crystallinities, thermal stabilities, surface morphologies, and porosities of these three new CMPs. Brunauer–Emmett–Teller (BET) analyses and tests of photocatalytic H2 production revealed that Py–TPA-CMP displayed the highest BET surface area (454 m 2 g −1 ), highest total pore volume (0.28 cm 3 g −1 ), highest H2 evolution rate (19 200 μmol h −1 g −1 ), and highest apparent quantum yield (15.3%) when compared with those of Py–F-CMP, Py–TPE-CMP, and other organic porous materials.